Chemical warfare agents decontamination via air mircoplasma excited by a triboelectric nanogenerator. (May 2022) - Bai, Yuan; Chen, Shubin; Wang, Huiyan; Wang, Engui; Kong, Xianghao; Gai, Yansong; Qu, Xuecheng; Li, Qi; Xue, Shuang; Guo, Peiwen; Wang, Ruixue; Feng, Hongqing; et al.
Abstract: Low-temperature air plasma, as an emerging green and efficient technology, has great potential to do chemical warfare agents (CWAs) decontamination. However, conventional plasma devices are bulky, costly and inconvenient. More importantly, their practical application is limited by the power grid and battery capacity. Here, A double layer paper-strip rotary triboelectric nanogenerator (dps-rTENG) is fabricated to serve as a self-powered high-voltage device to induce microplasma in air for CWAs decontamination. The degradation efficiency of 2-chloroethylethyl sulfide (2-CEES), a surrogate for the sulfur mustard (HD), reaches more than 99% within 2 min of microplasma treatment, and the energy utilization efficiency ( E e ) of the dps-rTENG is calculated to be 0.520 μg/J, which is one order of magnitude higher than those of the commercial power supplies. Further study confirms that the degradation process of the dps-rTENG induced microplasma is well controllable to avoid the formation of large amounts of 2-chloroethyl ethyl sulfone (2-CEESO2 ), a toxic excessive oxidation product. Triboelectric microplasma provides a new approach for self-powered, easily portable decontamination system for CWAs in future. Graphical Abstract: ga1 Highlights: Dps-rTENG is fabricated which can successfully induce microplasma in air. 40 μL of 100 mg/L 2-CEES can be completely degraded by the triboelectric microplasma within 2 min The energy efficiency of TENG is 0.520 μg/J, which is one order of magnitude higher than commercial power supplies. This system can effectively control the generation of toxic 2-CEESO2 . The negative DC and AC discharge modes have better degradation efficiency than positive DC.